INOVASI PEMANFAATAN LIMBAH DAUN TURI (SESBANIA GRANDIFLORA) SEBAGAI PUPUK ORGANIK CAIR (POC) UNTUK MENDUKUNG PERTANIAN DAN PETERNAKAN BERKELANJUTAN - Bagus Dimas Setiawan; Sumini; Judo Laksono; Syintia Dwi Agustina (JANITA : JURNAL PENGABDIAN KEPADA MASYARAKAT, 2026)
The underutilization of organic waste, particularly Sesbania grandiflora leaves, represents both a challenge and an opportunity in supporting sustainable agricultural and livestock systems. This community service activity was conducted with the Karya Makmur Farmers Group in Air Satan Village, aiming to enhance farmers’ knowledge and skills in processing turi leaves into liquid organic fertilizer (LOF). The methods employed included counseling, training on the production of LOF based on local microorganisms (MOL), and assistance in its application for crops and integration into livestock systems. The results showed that the members of the farmers group were able to understand the production process and independently produce LOF. The resulting LOF can be utilized to improve soil fertility, promote plant growth, and serve as a supporting material in livestock feed fermentation. Furthermore, this activity contributed positively by reducing organic waste, lowering production costs, and increasing awareness of environmentally friendly agricultural practices. Therefore, the innovation of utilizing turi leaf waste into LOF can serve as a practical solution to support sustainable agriculture and livestock systems at the community level.